2009
DOI: 10.1016/j.virol.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional and genetic analysis of coreceptor usage by dualtropic HIV-1 subtype C isolates

Abstract: It is widely documented that a complete switch from the predominant CCR5 (R5) to CXCR4 (X4) phenotype is less common for HIV-1 subtype C (HIV-1C) compared to other major subtypes. We investigated whether dualtropic HIV-1C isolates represented dualtropic, mixed R5 and X4 clones or both. Thirty of 35 functional HIV-1 env clones generated by bulk PCR amplification from peripheral blood mononuclear cells (PBMCs) infected with seven dualtropic HIV-1C isolates utilized CXCR4 exclusively. Five of 35 clones displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
0
13
4
Order By: Relevance
“…V3 loop characterization confirmed previous findings in which X4 viruses had a more variable crown motif, longer length, and higher V3 net charges than R5 viruses. 11,18 In contrast to other studies, 11,17,18 these characteristics were not found in the majority of D/M viruses except for a V3 net charge above + 4.5 in 58.8%. The efficiency of genotypic predictions based on V3 loop sequences was also investigated with C-PSSM sinsi having the highest sensitivity and relatively high specificity for predicting CXCR4 usage (75.0 and 87.5%, respectively).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…V3 loop characterization confirmed previous findings in which X4 viruses had a more variable crown motif, longer length, and higher V3 net charges than R5 viruses. 11,18 In contrast to other studies, 11,17,18 these characteristics were not found in the majority of D/M viruses except for a V3 net charge above + 4.5 in 58.8%. The efficiency of genotypic predictions based on V3 loop sequences was also investigated with C-PSSM sinsi having the highest sensitivity and relatively high specificity for predicting CXCR4 usage (75.0 and 87.5%, respectively).…”
Section: Discussioncontrasting
confidence: 73%
“…Second round PCR was carried out using Phusion Hot Start High-Fidelity DNA Polymerase (Finnzymes, Finland) with primers ENV1Adir and ENVM. 17 Second round cycling conditions were at 98°C for 30 s, followed by 35 cycles at 98°C for 10 s, 65°C for 30 s, and 72°C for 4 min, followed by a final extension at 72°C for 10 min. Amplified products were gel purified using the QIAquick Gel Extraction kit (Qiagen) and cloned and sequenced as previously described with the ABI Prism 3130xl Genetic Analyzer (Applied Biosystems, Foster City, CA).…”
Section: -15mentioning
confidence: 99%
See 1 more Smart Citation
“…cDNA synthesis, envelope amplification and cloning were done as previously described 25 . Full-length env from 20 ARV-failing patients and 20 ARV-naïve patients was cloned into the pcDNA3.1D/V5-His-TOPO vector (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Pseudoviruses were produced by co-transfection of Env expression plasmid and backbone pNL4-3. Luc.E-R-, as described previously [41,42]. Pseudovirus stocks were normalized with p24 ELISA prior to testing infectivity.…”
Section: Methodsmentioning
confidence: 99%